Religião e interioridade: o bem e o mal na vida de Martinho Lutero com o enfoque psicanalítico de Erik H. Erikson - Fonseca, Roberto Silva (2008)
The aim of his paper is to analyze Martin Luther s life, from the psychoanalytic view-point, by studying Erik Erikson s book Young Man Luther , A Study in Psychoanalysis and History. It is a very challenging bibliographic research, due to the amount of material produced up to now on Luther s life. A psycho-biography that aspires developing a profound and comprehensive study of a person whose magnitude of references is so vast is not an easy task. The first chapter s goal is to set up historical-scientific approach of the two protagonists. An exposition of Martin Luther s personal life is detailed firstly, beginning with his parents, reaching his individuality and his relationships with his wife and children. After that, a section will also be dedicated to Erik Erikson s life and thoughts, since he is taken as the point of theoretical reference to this piece of work. The second chapter consists in A Critical Dialogue With Erikson s Theory About Luther, elaborating a critical analysis of Erikson s book, Young Man Luther. This appreciation will be made on basis of the author of this paper s own thoughts, of ideas expressed by Luther himself, and of what other biographers have exhaustively spoken and written about his life. Finally, a critical appreciation and particular conclusions about the main characters will be expressed.